An evaluation of modifications to NHS Health Checks: A study protocol - Nigel Lloyd; Charis Bontoft; Katherine Barrett; John Jackson; Julia Jones; Lisa Miners; Nigel Smeeton; Adam P. Wagner; Amander Wellings; Katherine Brown (PLoS ONE, 2025)
Cardiovascular disease (CVD) is the leading cause of death globally; in the UK it contributes to a quarter of all deaths. In 2009, the UK National Health Service launched the NHS Health Check (NHSHC) programme to address CVD by assessing all adults aged between 40 and 74 years for CVD risk factors. Encouraging uptake of NHSHCs has proved challenging and areas for development have been identified nationally, prompting modifications to NHSHC practice in some localities. This protocol article describes a programme of research that will evaluate the impact of NHSHC modifications on attendance and outcomes in a large English local authority area. Modifications to NHSHC delivery (delivery of a modified NHSHC by a healthy lifestyle service rather than via general practice led delivery) and NHSHC invitation processes (implementation of text message prompts and reminders and an additional online booking option) will be evaluated. The research consists of six workstreams within a mixed methods framework: 1) Quantitative analysis of client NHSHCs records; 2) Focus groups with healthy lifestyle staff involved in coordinating and delivering the modified NHSHCs sessions; 3) Interviews with staff from pilot GP practices whose roles involve the coordination or delivery of NHSHCs; 4) Interviews with clients who have attended a healthy lifestyle service NHSHC; 5) Health economic resource and cost evaluation; 6) Data analysis, synthesis, and dissemination. The research programme’s breadth and its novel nature, mean that it will provide valuable findings for those commissioning and delivering NHSHCs nationally, and for the wider public health community.